LC-ESI-LTQ-Orbitrap-MS for Profiling the Distribution of Oleacein and Its Metabolites in Rat Tissues - Anallely López-Yerena; Anna Vallverdú-Queralt; Rosa M. Lamuela-Raventós; Elvira Escribano-Ferrer (MDPI AG, 2021)
The purpose of this work was to study the distribution of oleacein (OLEA) and its metabolites in rat plasma and different tissues, namely brain, heart, kidney, liver, lung, small intestine, spleen, stomach, skin, and thyroid, following the acute intake of a refined olive oil containing 0.3 mg/mL of OLEA. For this purpose, a distribution kinetics study was carried out. The plasma and tissues were collected at 1, 2, and 4.5 h after the intervention, and analyzed by LC-ESI-LTQ-Orbitrap-MS. Unmetabolized OLEA was detected in the stomach, small intestine, liver, plasma and, most notably, the heart. This finding may be useful for the development of new applications of OLEA for cardiovascular disease prevention. Noteworthy are also the high levels of hydroxytyrosol (OH-TY) and OLEA + CH3 found in the small intestine, liver, and plasma, and the detection of nine OLEA metabolites, five of them arising from conjugation reactions. Liver, heart, spleen, and lungs were the target tissues where the metabolites were most distributed. However, it is important to note that OH-TY, in our experimental conditions, was not detected in any target tissue (heart, spleen, thyroids, lungs, brain, and skin). These results shed further light on the metabolism and tissue distribution of OLEA and contribute to understanding the mechanisms underlying its effect in human health.